1998
DOI: 10.1002/lt.500040103
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hepatitis C virus genotypes on the outcome of liver transplantation

Abstract: Background: The aim of this study was to report the influence of hepatitis C virus (HCV) genotypes and HLA matches on the outcome of liver transplantation, hepatitis recurrence, and progression to cirrhosis after transplantation. Methods: HCV genotypes were determined from pretransplantation sera and/or liver explant tissues from 202 patients with HCV-related end-stage liver disease. One hundred fifty patients with known infecting genotype for whom posttransplantation biopsy specimens were available or who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
56
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 30 publications
2
56
1
Order By: Relevance
“…Several groups have suggested that infection with HCV genotype 1b is associated with a higher recurrence rate 21 and more severe posttransplantation hepatitis. 22,23 However, a large study based on patients in a major liver center in the United States did not confirm this association 10 24 In this large series of patients, most of whom developed chronic hepatitis within 5 years of follow-up, the authors found no correlation between HCV genotypes and the outcome of recurrent posttransplantation hepatitis as measured by overall patient survival, liver disease-free interval, and severity of histological disease. In particular, patients infected with HCV genotype 1 (or subtype 1b) had similar clinical and histological outcomes compared with those infected with other viral genotypes.…”
Section: Viral and Host Factorsmentioning
confidence: 79%
See 3 more Smart Citations
“…Several groups have suggested that infection with HCV genotype 1b is associated with a higher recurrence rate 21 and more severe posttransplantation hepatitis. 22,23 However, a large study based on patients in a major liver center in the United States did not confirm this association 10 24 In this large series of patients, most of whom developed chronic hepatitis within 5 years of follow-up, the authors found no correlation between HCV genotypes and the outcome of recurrent posttransplantation hepatitis as measured by overall patient survival, liver disease-free interval, and severity of histological disease. In particular, patients infected with HCV genotype 1 (or subtype 1b) had similar clinical and histological outcomes compared with those infected with other viral genotypes.…”
Section: Viral and Host Factorsmentioning
confidence: 79%
“…In this issue, Varga et al also address this question and, on the basis of serological assays for the HLA class I and II typing, the authors found no association between degree of HLA matching and incidence or severity of recurrent HCV-associated liver disease after transplantation. 24 A similar lack of correlation between the degree of HLA matching and the outcome of liver disease after transplantation has also been demonstrated using more accurate molecular-based assays to determine HLA II. 22 Can We Have Conclusions?…”
Section: Viral and Host Factorsmentioning
confidence: 83%
See 2 more Smart Citations
“…11,12 In liver transplant recipients, the course of HCV-induced liver injury is accelerated, with HCV recurrence apparent histologically in approximately 50% of HCVinfected transplant recipients and HCV-associated allograft failure leading to death or graft loss in approximately 10% of transplant recipients by the fifth postoperative year. 2,3,7,10,[13][14][15][16][17] Greater pretransplantation levels of viremia have been associated with attenuated patient and allograft survival among HCV-infected liver transplant recipients. 7 The National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) Liver Transplant Database reported that patients with lower levels of hepatitis C viremia (Ͻ1 ϫ 10 6 viral copies/mL) before liver transplantation had a significantly lower risk for mortality and allograft loss compared with patients with greater levels.…”
mentioning
confidence: 99%